## Active forum topics

- Eliminate the Arbitrary Constants
- Law of cosines
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Integration of 4x^2/csc^3x√sinxcosx dx
- application of minima and maxima
- Sight Distance of Vertical Parabolic Curve
- Application of Differential Equation: Newton's Law of Cooling
- Minima maxima: a²y = x⁴
- Trim and stability

## New forum topics

- Integration of 4x^2/csc^3x√sinxcosx dx
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Newton's Law of Cooling
- Law of cosines
- Can you help me po to solve this?
- Eliminate the Arbitrary Constants
- Required diameter of solid shaft
- Differentiate trigonometric function
- Integration $\displaystyle \int \sec 2x ~ dx$

## Recent comments

- Mali po ang equation mo…1 week ago
- $x$ is the location where…1 week ago
- In double integration method…1 week 4 days ago
- Maayo, salamat sa imong…3 weeks ago
- 24 ft during the 10th second…3 weeks ago
- The differentiation you need…3 weeks ago
- Obtain the differential…3 weeks 1 day ago
- Thank you for sharing your…3 weeks 1 day ago
- Based on the differentiation…1 week 4 days ago
- Given that $x + y + xy = 1$,…1 week 4 days ago

## We need to reaarange the

We need to reaarange the differential equation so that it can be solved easily...

$$\left( x \csc\left( \frac{y}{x}\right) - y\right) dx + x dy = 0$$

$$x \csc\left( \frac{y}{x}\right)dx - ydx + xdy = 0$$

$$xdy = -x \csc\left( \frac{y}{x}\right)dx + ydx$$

Divide the terms of the differential equation by $x$, getting:

$$dy = - \csc\left( \frac{y}{x}\right)dx + \left( \frac{y}{x}\right)dx$$

Apparently this modified form of differential equation is a homogenous differential equation. So we let $v = \frac{y}{x}$, $y = vx$ and

$dy = vdx + xdv$. So we get:

$$dy = - \csc\left( \frac{y}{x}\right)dx + \left( \frac{y}{x}\right)dx$$

$$vdx + xdv = - \csc(v)dx + vdx$$

$$ xdv = - \csc(v)dx$$

$$\frac{dv}{-\csc(v)} = \frac{1}{x} dx$$

$$-sin(v)dv = \frac{1}{x} dx$$

The above differential equation is now a variable-separable type...so we get the integral of individual terms.

$$-sin(v)dv = \frac{1}{x} dx$$

$$\int -sin(v)dv = \int \frac{1}{x} dx$$

$$cos(v) + c_1 = ln(x) + c_2$$

$$cos(v) = ln(x) + c_2 - c_1$$

$$cos(v) = ln(x) + C$$

Now getting the $v$:

$$cos(v) = ln(x) + C$$

$$v = cos^{-1}(ln(x) + C)$$

The solution of the given differential equation $\left( x \csc\left( \frac{y}{x}\right) - y\right) dx + x dy = 0$ would be:

$$y = vx$$

$$y = (cos^{-1}(ln(x) + C))x$$

$$y = xcos^{-1}(ln(x) + C)$$

Alternate ways of answering it are encouraged....